1 × 2 1 + 1 × 5 1 + 3 × 3 1 + 2 × 7 1 + 5 × 4 1 + …
Find the sum of this infinite series.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thanks for explaining how one can interpret and understand the series as stated.
Log in to reply
You're welcome Sir!
So . here means multiplication? that's ambiguous
2 ( 1 . 4 1 + 2 . 5 1 + 3 . 6 1 + 4 . 7 1 + 5 . 8 1 + … )
= r = 1 ∑ n r ( r + 3 ) 2
= 3 2 ( r = 1 ∑ n r 1 − r + 3 1 )
= 3 2 ( 1 + 2 1 + 3 1 − ( n + 1 1 + n + 2 1 + n + 3 1 ) )
= 9 ( n + 1 ) ( n + 2 ) ( n + 3 ) n ( 1 1 n 2 + 4 8 n + 4 9 )
For large n , we just look at the n 3 term, so it is 9 1 1 = 1 . 2 2 2 2 … .
= 1 × 2 1 + 1 × 5 1 + 3 × 3 1 + 2 × 7 1 + … = n = 1 ∑ ∞ 2 n ( n + 1 ) + n 1 = n = 1 ∑ ∞ n 2 + 3 n 2 = 2 n = 1 ∑ ∞ n ( n + 3 ) 1 = 3 2 n = 1 ∑ ∞ ( n 1 − n + 3 1 ) = 3 2 ( n = 1 ∑ ∞ n 1 − n = 4 ∑ ∞ n 1 ) = 3 2 ( 1 + 2 1 + 3 1 ) = 3 2 ⋅ 6 1 1 = 9 1 1 = 1 . 2 2
How did you realise that the denominator could be written like 2 n ( n + 1 ) + n ?
The denominator pattern suggested is one that fits the given terms, but there are others resulting in different sums. A classic sequence related to geometry begins 1, 2, 4, 8, 16, 31, ... (not binary) for another example of this concern.
Therefore this problem is not, in the parlance of mathematicians, "well posed". Without a defining rule for computing the terms, a sequence can be devised to have whatever sum you want to give it!
Call the sum as S n . Then S n = 2 1 + 5 1 + 9 1 + 1 4 1 ⋯ = 3 − 1 1 + 6 − 1 1 + 1 0 − 1 1 + 1 5 − 1 1 + ⋯ = n = 2 ∑ ∞ n ( n + 1 ) − 2 2 = n = 2 ∑ ∞ ( n − 1 ) ( n + 2 ) 2 = 3 2 n = 2 ∑ ∞ ( n − 1 1 − n + 2 1 ) = 3 2 n = 1 ∑ ∞ ( n 1 − n + 3 1 ) = 3 2 ( 1 + 2 1 + 3 1 ) = 9 1 1 = 1 . 2 2 2 2
Problem Loading...
Note Loading...
Set Loading...
If we observe the denominators, 2 , 5 , 9 , 1 4 , 2 0 , ⋯ ⋯ We can see that the difference between two consecutive is in an A.P. with common difference 1. Hence we can find the n t h term. n t h t e r m = T n = 2 ( n + 1 ) ( n + 4 ) So, n t h term of given sequence is T n 1 . To get first term, put n = 0 ,
To get second term put n = 1 , and so on.
Now we have to find sum of first 1 0 0 terms, i.e. n = 0 ∑ 9 9 T n 1 = n = 0 ∑ 9 9 ( n + 1 ) ( n + 4 ) 2 = 3 2 n = 0 ∑ 9 9 ( n + 1 1 − n + 4 1 )
All of the terms cancel out except the first three terms, and three terms at the end which are essentially 0. Thus, we have 3 2 ( 1 + 2 1 + 3 1 ) = 1 . 2 2 2 2 2 2 2 …